2007
DOI: 10.1002/sia.2483
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of COO2 gas mixtures with Au tips: in situ imaging and local chemical probing

Abstract: The interaction of CO/O 2 gas mixtures with gold has been studied by means of video-field ion microscopy (FIM) under truly in situ conditions on the surfaces of small Au tips. To elucidate the local surface composition while imaging, atom-probe studies have been performed using field pulses in a pulsed field desorption mass spectrometry (PFDMS) set-up. The interaction of pure CO with Au field-emitter tips at 300 K causes Au carbonyl to be formed on the surface, and these appear as singly and doubly charged cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Small nanoclusters may also be able to activate O 2 . Field-ion microscopy experiments have shown that a Au tip can change in response to an O 2 atmosphere, and it was proposed that a surface oxide was formed . However, several later studies show negligible O 2 dissociation or catalytic activity for nanostructured Au, even for Au nanoparticles on non-oxide supports. , Recently, experimental and computational work have suggested that twinning sites on nanostructured Au may be able to catalyze CO oxidation by O 2…”
Section: Mechanisms and Barriers For O2 Dissociationmentioning
confidence: 99%
“…Small nanoclusters may also be able to activate O 2 . Field-ion microscopy experiments have shown that a Au tip can change in response to an O 2 atmosphere, and it was proposed that a surface oxide was formed . However, several later studies show negligible O 2 dissociation or catalytic activity for nanostructured Au, even for Au nanoparticles on non-oxide supports. , Recently, experimental and computational work have suggested that twinning sites on nanostructured Au may be able to catalyze CO oxidation by O 2…”
Section: Mechanisms and Barriers For O2 Dissociationmentioning
confidence: 99%
“…One of the advantages of this technique is to allow the study of catalytic reactions in the absence of any influence of the oxidic support, which is of great importance for the fundamental understanding of the catalytic system. In addition to this, the behaviours observed are influenced by the presence of a steady electric field which could mimic conditions encountered in studies over Au δ+ /metal-oxide catalysts [196]. In Figure 13a, we can observe a typical Au sample prepared and imaged by field ion microscopy.…”
Section: Processes On Au Tips Propagation Waves During Co/o 2 Interacmentioning
confidence: 79%
“…Nonetheless, it has been shown that the catalytic contribution of silver is crucial [35,36]. As compared to pure Au [37][38][39], Ag has much stronger interactions with oxygen [40,41] and can therefore be considered as the atomic oxygen provider in Au-Ag based catalysis for oxidation reactions.…”
Section: Au-88%at Ag Exposure To Nomentioning
confidence: 99%